Vinco Trumpos XIX a. Lietuvos istorijos modelis - Kulakauskas, Antanas (Lietuvos istorijos studijos, 1997)
The present paper continues discussion on Vincas Trumpa, which started some time ago in the cultural journal „Baltos lankos." I should admit that in my previous publication the difference between historic and retrospective approaches and their principles was not stated enough. It seems that the principles of the historical approach require no comments. I have had in mind that what concerns retrospection, while using the nation, attempts to model the past on the basis of contemporary society, its values included. No doubt, the idea of an independent, national Lithuanian state became a reality of social life at the end of the 19th century; however, the interpretation of 19th century Lithuanian history from the retrospective viewpoint seems to be debatable. I have called the approach „national" in the wide sense, though I have no doubts about the liberal position of my opponents.